IMPLEMENTASI APLIKASI PALAPA MOJO DALAM MENINGKATKAN INTEGRASI PELAYANAN PUBLIK DI KOTA MOJOKERTO - khayati, elly nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
This study examines the implementation of the Palapa Mojo application in enhancing public service integration in Mojokerto City. Using a descriptive qualitative approach and Van Meter and Van Horn's (1975) policy implementation theory, the research finds that the application has improved efficiency, transparency, and inter-agency synergy through digitalization. However, technical issues such as system errors and lack of socialization hinder its optimal use. The results indicate that successful implementation is influenced by clear policy standards, internal resources, inter-organizational communication, and positive responses from implementers. Recommendations include technological improvements, intensive socialization, and dedicated budget allocation for sustainable development.Keywords : Palapa Mojo, public service integration, policy implementation, Van Meter and Van Horn, Mojokerto City.